English Literature from the Other Perspective: A Thought and an Approach - Salma, Umme (IIUC Studies, 2015)
English Literature as the knowledge of the former master is an exclusively challenging discipline to be focused from the Other perspective, from Muslim perspective, one among many Others. It is a bellicose field because in the postcolonial world its presence reminds of the colonial past, and declares the continuance of the myriad ideological projections and paradigmatic speculations of that past in the neocolonial form. Still postcolonial Indian Muslim societies are promoting and propagating English knowledge in every stage of educational institutions, and thus creating a culturally hybrid/syncretic nation which can neither accept Englishness entirely nor reject its own cultural inheritance and realities totally. Whereas other postcolonial nations can approve, accept and accelerate the mixed-up jumbled cultural syncretism gradually losing or conforming their native cultural signifiers with Western culture, Muslims cannot because the ideology and approach to life of Islam are straightly opposite to the English knowledge, emanated from the Judeo-Christian and Greco-Latin cultural heritage. Keeping in view the aforementioned ideas, the paper argues that this is high time to review this epistemological crisis from historical set up and to read English literature from the Other point of view. Therefore, it proposes some ways to re-read the English canonical compositions and puts forward as specimen the re-reading/teaching method of ENG: 2420, titled English Poetry: 17th &18th Centuries from the undergraduate syllabus of IIUC. IIUC Studies Vol.9 December 2012: 261-278